IMPLEMENTATION OF NATIONAL EDUCATION STANDARDS IN IMPROVING THE QUALITY OF EDUCATION - Mesiono Mesiono; Putra Mahendra Gunawan Nasution; M. Ali Napiah; Rahmat Hidayat (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Schools become very important to be established in various regions in Indonesia, on the other hand, the schools established must also be quality, the quality of a school is seen by its quality. Quality schools are schools that refer to the National Standard of Education which contains content standards, process standards, graduation competency standards, educator and education personnel standards, facilities and infrastructure standards, management standards, financing standards, and assessment standards. This research aims to determine the implementation of the National Education Standard to improve the quality of education in MTsN-2 Tapanuli Tengah. This research uses qualitative descriptive approach methods that aim to understand circumstances or phenomena using description in the form of words or language and describe real events encountered in the field. Data collection techniques from these studies use methods of observation, interview, and documentation. The data analysis techniques used in this study through 3 activity flows, namely data reduction, data presentation, and data verification. The results of this study are the application of management functions, namely management functions in planning, implementation, and supervision and connecting with the implementation of the National Education Standard on planning, implementation of national education standards on the implementation, and implementation of national standards of education on supervision. According to researchers, MTsN-2 Tapanuli Tengah has implemented 8 National Standards of Education so the head of the madrasah hopes that the accreditation of MTsN-2 Tapanuli Tengah can increase from year to year.